An Analysis of Teachers’ Perceptions toward the Role of ICT Based Media in Teaching and Learning Process among Primary Schools’ Teachers - Rahmi, Regina; Fitriati, Fitriati; Fachraini, Siti (SCAD Independent, 2019)
Development in technology assists teachers and educators to reach goals in teaching and learning easily. Along with advancement of technology in teaching, teachers were expected to utilize this technology such as ICT-based media to improve quality of their teaching. This paper was a survey research which tried to investigate attitudes and perceptions of 73 elementary school teachers toward the use of ICT-based media especially video in teaching learning process. Both quantitative and qualitative data were used to display teachers’ perception. The result of this study shows that almost all teachers considered that using media is very important in teaching. The data from questionnaires shows that most teachers (95,1%) agreed that ICT-based media made teaching and learning process more enjoyable and effective. They also believed that the role of media together with teacher is essential in teaching since the collaboration between teachers and media allow students to understand and memorize materials given easily. However, besides teachers responded positively toward ICT-based media, they also encountered some barriers in applying this technology in teaching, such as : teachers lacked the skills or basic concepts about ICT, (felt were old enough) to use ICT based-media in the future, lacked of eyes vision, inconvenience feeling of using ICT in the classroom, and lacked of ICT facilities at school. This indicates that professional development program is essential for teachers to promote the use of technology in daily teaching practices.